Effect of ionic liquids as active pharmaceutical ingredients on the micellar binding of an amphiphilic drug trifluopromazine hydrochloride - GÖKTÜRK, SİNEM (TAYLOR & FRANCIS INC, 2021)
This work deals with the effect of ionic liquids (ILs), 1-ethyl-3-methyl imidazolium chloride (EmimCl), and 1-butyl-3-methyl-imidazolium chloride (BmimCl) on the interaction and binding properties of the antidepressant phenothiazine drug, trifluopromazine hydrochloride (TFP) with nonionic surfactants (Brij 30, Brij 35, and Brij 56). Absorption and surface tension measurements have been performed in order to study the nature of interactions between drug and nonionic surfactant mixtures in the absence and presence of ILs. To explain the binding mechanism corresponding parameters such as maximum surface excess concentration at the air-water interface (?(max)), minimum area per surfactant molecule (A(min)), and micellar binding constant (K-B) have been calculated by employing the theoretical models Gibbs Adsorption Isotherm and Benesi-Hildebrand Equation, respectively at 298?K. Surface properties of surfactant solutions in the presence of ILs were also compared to those of bulk water in order to see the influence of the ILs on the micellar binding of TFP.
Keywords: Amphiphilic drug; binding; ionic liquids; interaction; surfactants; SODIUM DODECYL-SULFATE; AMITRIPTYLINE HYDROCHLORIDE; ZWITTERIONIC SURFACTANT; MICELLIZATION BEHAVIOR; AGGREGATION BEHAVIOR; MIXTURES; PROMETHAZINE; SOLVENTS; CHLORIDE; PHASE